Say it right 1 - Kirkpatrick, Betty (Learners Publishing Pte Ltd, 2006)
Say it right 1 and 2 are intended to help learners master social english expressions so that they can readily engage in social communication. Each book explains the most important phrases that are commonly associated with a particular social situation, followed by a coupje os lively dialogue in which these phrases are used.